2008
DOI: 10.1007/s11172-008-0078-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-diffusion in the isotropic and mesomorphic states of the lanthanide-containing system based on nonionic surfactant according to the NMR data

Abstract: Molecular self organization in a system based on lanthanum nitrate and the nonionogenic surfactant, viz., decaethylene glycol monododecyl ether, was studied in an aqueous solution and in the liquid crystalline state. Molecular motion and phase transitions in the system were characterized by the high resolution pulsed gradient spin echo 1 H NMR method.Considerable attention is presently given to studies of the structural and phase properties of lyotropic liquid crystals (LLC). 1-5 Metal containing LLC are widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Despite increased interest in lyotropic metallomesogens, there is rather limited number of studies dedicated to lanthanidecontaining lyotropic phases. [24][25][26][27][28] The present study continues our research on the synthesis and characterization of lanthanidecontaining lyotropic liquid crystals based on oxyethylated surfactants. This work is aimed at finding a correlation between the molecular structure of amphiphilic molecules and supramolecular organization in the mesophases containing a lanthanide ion.…”
Section: Introductionmentioning
confidence: 58%
“…Despite increased interest in lyotropic metallomesogens, there is rather limited number of studies dedicated to lanthanidecontaining lyotropic phases. [24][25][26][27][28] The present study continues our research on the synthesis and characterization of lanthanidecontaining lyotropic liquid crystals based on oxyethylated surfactants. This work is aimed at finding a correlation between the molecular structure of amphiphilic molecules and supramolecular organization in the mesophases containing a lanthanide ion.…”
Section: Introductionmentioning
confidence: 58%
“…In our earlier papers, we first discussed synthesis of lanthanide containing LLC systems, based on nonionic surfactants made up of decaethylene glycol monododecyl ether and tetraethylene glycol monododecyl ether, which are stable over a wide range of temperatures (including room temperature) and concentrations. Self-organizing processes in solutions and mesophases were investigated. It was shown that the luminescence efficiency depends on the liquid crystal phase orientation. The luminescence efficiency demonstrated a 7-fold increase when a transition from unoriented samples to oriented samples occurred .…”
Section: Introductionmentioning
confidence: 99%